Perizinan Berusaha dalam Perspektif Hukum Administrasi Negara dan Ekonomi - Zulfikar Ali; Intan Meitasari; Yuniwati Yuniwati (Journal of Law and Economics, 2026)
This study examines the role of State Administrative Law in promoting efficiency in the economic sector and social welfare through business licensing regulations. This issue is important because business licensing is not only an instrument of government control but also influences business actor behavior, transaction costs, legal certainty, and market competitiveness. The purpose of this study is to analyze government authority in terms of business licensing regulations and assess the extent of its influence on economic efficiency and public welfare. This study uses a normative juridical method with a statutory regulatory approach and a conceptual approach. Data were collected through a literature review of statutory regulations, state administrative law literature, and legal and economic studies. The analysis was conducted qualitatively by examining the relationship between administrative authority, licensing services, business actor compliance, and their impact on economic activity. The results of this study indicate that simple, transparent, and accountable business licensing can reduce bureaucratic barriers, increase compliance, and create certainty for business actors. Thus, State Administrative Law contributes significantly to building efficient, fair, and social welfare-oriented economic governance.